Synthetic aperture-based beam compression for intravascular ultrasound imaging - Vray, D (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2001)
In this paper, intravascular ultrasound (IVUS) images acquired with a 64-element array transducer using a multistatic acquisition scheme are presented. The images are reconstructed from a collection of pulse-echo measurements using a synthetic aperture array imaging technique. The main limitations of IVUS imaging are a poor lateral resolution and elevated grating lobes caused by the imaging geometry. We propose a Synthetic Aperture Focusing Technique (SAFT), which uses a limited number of A-scan signals. The focusing process, which is performed in the Fourier domain, requires far less computation time than conventional delay-and-sum methods. Two different reconstruction kernel functions have been derived and are compared for the processing of experimental data